Genetic Characterization of ABL1 Inhibition and Regulation by the Tumor Suppressor PRDX1. - Salazar, Marcos. (2017)
Abstract: The first portion of this thesis serves to further characterize the roles of PRDX1, mainly focusing on ABL1 regulation and oxidative stress. Our laboratory first discovered PRDX1 physically binds to c-ABL1 and suppresses its kinase activity. However, the interaction is not well defined. We found imatinib-resistant ABL1 kinase mutations, which are commonly seen in BCR-ABL1 of CML patients, were also resistant to PRDX1 suppression. Other studies in our lab also demonstrated that mice lacking Prdx1 acquire various types of age-dependent cancers. A growth delay was observed in primary Prdx1-/- MEFs, so we exploited this observation, as it may influence oncogenesis. We found that PRDX1 antioxidant activity plays a role in maintaining cell survival. In the absence of PRDX1, oxidative stress seems to contribute to the growth delay, and possibly leads to a cancerous phenotype. In an effort to better understand BCR-ABL1 regulation and signaling, the second portion of this thesis focuses on PRDX1 activity and its possible functional role in BCR-ABL1-mediated transformation and leukemogenesis. BCR-ABL1 is a constitutively active tyrosine kinase known to cause chronic myeloid leukemia (CML) and, in some instances, acute B lymphoblastic leukemia (B-ALL). As the biomedical community strives to find better chemotherapeutic drugs to target and eliminate leukemic cells, it is of great importance to also understand what leads to leukemia development and progression at the genetic and molecular levels. Although there are currently extensive studies attempting to understand the signaling mechanisms elicited by BCR-ABL1, the disease is still not completely understood. Because PRDX1 was previously found to partially inhibit BCR-ABL1 kinase activity, we hypothesized it may be a candidate protein regulating leukemic transformation and leukemogenesis. Our in vitro data show that in the absence of Prdx1, BCR-ABL1 tyrosine kinase activity is elevated, leading to enhanced transformation potential, an increase in cell survival and proliferation, and stimulation of malignant growth within the lymphoid lineage. Loss of Prdx1 also initiates disease development at a slightly faster rate in our B-ALL murine model system. Other experiments also prove PRDX1 regulation plays a role in myeloid transformation and leukemogenesis. Bone marrow cells lacking Prdx1 show enhanced BCR-ABL1-mediated myeloid transformation. In addition, BCR-ABL1, in the absence of Prdx1, elicits a more aggressive leukemia phenotype in the CML murine model system. Together, the results presented in this thesis demonstrate that PRDX1 functions to suppress cell transformation and hematological malignancies induced by BCR-ABL1.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Genetics.; Advisors: Richard Van Etten, and Charlotte Kuperwasser.; Committee: Philip Hinds, and Peter Brodeur.; Keyword: Genetics.